Pengaruh Pembayaran Dividen Terhadap Kinerja Keuangan Perusahaan Pada Perusahaan Manufaktur Di BEI - Putri Nuriksani; Verina Puspa Sari (Jurnal Ekonomi, 2022)
The purpose of this study is to understand the effect of dividend policy on a company's financial performance. This article examines the research gap and then builds a research model using ROA as the dependent variable, dividend rate and dividend payment decision as independent variables, and firm size, leverage, and income growth as control variables. This paper collects data and financial reports from 196 companies from the manufacturing sector listed on the Indonesia Stock Exchange from 2016 to 2020. The results of the analysis show that dividend payment decisions have no effect on manufacturing companies as measured by the financial performance of accounting-based companies but this raises expectations. the market for the company. In addition, this paper finds that manufacturing companies offer low dividend rates which have a positive impact on the company's financial performance but have a negative effect on market expectations. This paper offers some informative results-based recommendations, including better dividend policy models, lower dividend yields, and clearer dividend payment decisions.